Prosedur Pengembangan Instrumen Tes Kreativitas Berbasis Indikator Berpikir Kreatif - Salsyabilla Putri Ramadhani; Aghniyah Nawfalah; Zaskia Rahmadina; Harla Wulandina; Minarsi Minarsi; Yola Eka Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This literature study examines the procedures for developing creativity test instruments based on creative thinking indicators in educational assessment. The background of this study is driven by the limited availability of appropriate instruments that can accurately measure students’ creative thinking skills, as most existing assessments still emphasize lower-order thinking. The objective of this study is to analyze systematic procedures in developing valid and reliable creativity test instruments. The method used is a qualitative literature review of various studies on instrument development, particularly those applying Research and Development (R&D) approaches such as 4-D models. The findings show that the development process generally involves several stages, including needs analysis, formulation of test specifications, construction of items based on creative thinking indicators (fluency, flexibility, originality, and elaboration), expert validation, limited trials, and statistical analysis of validity and reliability. These indicators represent core dimensions of creative thinking that must be integrated into the instrument to ensure comprehensive measurement . The implications of this study highlight that systematic and theory-based procedures are essential to produce high-quality instruments that are valid, reliable, and practical, thereby supporting effective evaluation and fostering students’ creative thinking skills.